Effect of Different Mixing and Placement Methods on the Compressive Strength of Calcium-Enriched Mixture - Sahebi, Safoora; Sadatshojaee, Nooshin; Jafari, Zahra (Iranian Endodontic Journal, 2015)
Introduction: The aim of this experimental laboratory study was to evaluate the effect of different mixing and placement techniques on compressive strength (CS) of calcium-enriched mixture (CEM) cement. Methods and Materials: CEM powder was mixed with its liquid either by hand mixing or amalgamator mixing. The mixture was loaded to cylindrical acrylic molds with 6.0±0.1 mm height and 4.0±1 mm diameter. Half of the specimens in each group were selected randomly and ultrasonic energy was applied to them for 30 sec. All samples were incubated for 7 days at 37°C. The CS test was performed by means of a universal testing machine. The data were analyzed by the two-way analysis of variance (ANOVA) and Tukey’s post hoc tests. The level of significance was set at 0.05. Results: The maximum CS was seen in the amalgamator-mixed samples that did not receive ultrasonic agitation. The CS value of amalgamator-mixed samples was significantly higher than manually-mixed ones (P=0.003). Ultrasonic vibration did not change the CS of specimens. Conclusion: According to the results, mixing with amalgamator increases the CS of CEM cement, while ultrasonic vibration had no positive effect